PEMBERDAYAAN AGAMA BAGI ANAK-ANAK MELALUI GERAKAN “MAGHRIB MENGAJI” DI DESA SEMANDING JENANGAN PONOROGO - Wahyuningtyas, Nofiya; Soraya, Siti Zazak (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
The selection of community service based on religious education, namely the reciting Al-Qur’an activity after performing the Maghrib prayer in Semanding Village, Jenangan District, Ponorogo Regency, is one of the efforts to facilitate children in learning the Al-Qur’an, which has not been available so far. The method used in implementing this community service is asset-based community development (ABCD). The community is the actor and determinant of development efforts in the environment or is often referred to as community-driven development (CDD). In addition to being a place or facility for learning the Al-Qur’an, this activity is expected to continue even after the Community Service Lecture period is over so that children have better Al-Qur’an skills. The positive impact given from the "Maghrib Mengaji" activity is that children are accustomed to reading the Al-Qur’an/volumes after performing the Maghrib prayers. In addition, children who previously had not memorized short letters now have memorized several short letters of Al-Qur’an.